Endoscopic diagnosis and treatment in urinary bladder pathology : handbook of endourology - Geavlete, Petrisor A. (Petrisor Aurelian) (Academic Press is an imprint of Elsevier, 2016)
"Endoscopic Diagnosis and Treatment in Urinary Bladder Pathology: Handbook of Endourology contains five focused, review-oriented volumes that are ideal for students and clinicians looking for a comprehensive review rather than a whole course. Topics covered review both the endourological diagnosis and treatment of prostate, urethral, urinary bladder, upper urinary tract, and renal pathology. All chapters describe the most recent techniques, review the latest results, and analyze the most modern technologies. In the past ten years, the field of endourology has expanded beyond the urinary tract to include all urologic minimally invasive surgical procedures. Recent advancements in robotic and laparoscopic bladder surgery make this one of the fastest moving fields in medicine. As current textbooks are too time-consuming for busy urologists or trainees who also need to learn other areas of urology, this collection provides quick references and over 4000 images that are appropriate for fellows and those teaching in the field"--Publisher's description